PENERAPAN SENAM HIPERTENSI SEBAGAI INTERVENSI NON-FARMAKOLOGIS PADA LANSIA DI PUSKESMAS ARJUNO KOTA MALANG - Lucia Retnowati; Aminatus Sulfa Laili Fitria; Agus Setyo Utomo (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Hypertension in the elderly poses significant health challenges, so effective non-pharmacological interventions are needed. This study aims to evaluate the effectiveness of hypertension gymnastics as a non-pharmacological intervention for elderly patients at the Arjuno Health Center, Malang City. The research method used was a qualitative case study, which involved two elderly subjects with hypertension over a period of two weeks. Data collection was carried out through in-depth interviews, direct observation, and blood pressure measurements before and after the gymnastics intervention. This hypertension gymnastics program includes light to moderate aerobic exercise and flexibility training. The results showed a consistent decrease in blood pressure in both participants, with an average decrease in systolic pressure of 10-15 mmHg and diastolic pressure of 5-10 mmHg over the study period. In addition, participants showed increased knowledge about hypertension management and motivation to engage in physical activity. Subjective symptoms such as headaches and sleep disturbances also improved. The effectiveness of hypertension exercises in this study was achieved through a dose of exercise in the form of a frequency of 4 times per week with a duration of 30 minutes per session, which was proven to provide a significant reduction in blood pressure. This gymnastics program emphasizes light to moderate intensity aerobic exercise, which has been shown to help improve cardiovascular function and lower vascular resistance. This research contributes to the development of scientific evidence regarding the effectiveness of structured gymnastics programs in the management of hypertension in the elderly. These results confirm the importance of hypertension gymnastics as an integral part of primary care strategies for hypertensive elderly patients, emphasizing the importance of a tailored non-pharmacological approach to improve blood pressure control and overall quality of life.